Ciência como técnica ou técnica como ciência: nas trilhas da Arquivologia e seu status de cientificidade - Silva, Luiz Eduardo Ferreira da (2013)
The research aims at understanding the scientificity character of Archival Science in light of Information Science so as this problematization may have an outstanding role in the archival context. In this way, the following hypothesis was taken into account: In the Archival Science, the logic of instrumental action hinders the field character as science when, in fact, it is unfolded as a technique. In this perspective, by means of the evidential method and the critical hermeneutics, we searched through interpretative evidence to find clues for the epistemological uncertainness in which the Archival Science is circumscribed, especially, in the theoretical and methodological context. Therefore, through this evidential action, the possibilities of an Archival Science technique or of an Archival Science - Science were measured. In effect, it was observed that the Archival Science can not ignore the technique as procedure, but one major concern is related to the scientification of the technique which became the Archival Science ideology; the first sense and the last one about which the reason of being is constituted as basis. Thereby, the evidential and interpretative results demonstrate that if the Archival Science is reduced to a set of techniques, it refers to a product and not to a science that, usually, produces truths and implements them by creating products. Consequently, it can be concluded that this study enabled to perceive that a reflective action in the context of Archival Science research can make the Archival Science to distance from the functional/pragmatic model that registered it in the historicization process.